2020
DOI: 10.1111/cts.12731
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Prediction Model of Vancomycin‐Associated Nephrotoxicity in Elderly Patients: A Pilot Study

Abstract: This exploratory study aimed to develop a risk prediction model of vancomycin-associated nephrotoxicity (VANT) in elderly patients. Clinical information of elderly patients who received vancomycin therapy from January 2016 to June 2018 was retrieved. A total of 255 patients were included in this study. Univariate analysis and multivariable logistic regression analysis revealed that vancomycin trough concentration ≥ 20 mg/L (odds ratio (OR) = 3.009; 95% confidence interval (CI) 1.345-6.732), surgery (OR = 3.357… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
11
1
1
Order By: Relevance
“…The proportion of average VCM concentrations ≥20 mg/L was only 15.7% (1146/7306 patients) and was not as high as those previously reported. 35,36 The median averages of VCM concentrations were 17.0 and 13.7 mg/L for patients with and without VIN, respectively. These values resembled those of our previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…The proportion of average VCM concentrations ≥20 mg/L was only 15.7% (1146/7306 patients) and was not as high as those previously reported. 35,36 The median averages of VCM concentrations were 17.0 and 13.7 mg/L for patients with and without VIN, respectively. These values resembled those of our previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results were reported by Chuma et al; 31 the rate of vancomycin-associated nephrotoxicity in patients with initial trough levels ≥20 µg/mL (31.3%) was significantly higher than that of patients with initial trough levels <10 µg/mL (6.3%). Moreover, a study by Pan et al 32 of patients aged ≥60 years found that VTC ≥20 µg/mL was an independent risk factor for vancomycin-associated nephrotoxicity and led to a 3-fold increased risk of nephrotoxicity. The present study is consistent with the clinical studies described above.…”
Section: Discussionmentioning
confidence: 99%
“…piperacillintazobactam, aminoglycosides) and renal insufficiency. Higher Charlson comorbidities, association with piperacillin-tazobactam or aminoglycosides, diuretics and previous renal insufficiency are related to vancomycin toxicity and unpredictable serum levels 29,32 .…”
Section: Discussionmentioning
confidence: 99%